Investigation on solvent-borne intumescent flame-retardant coatings for steel - Yew, M.C.; Sulong, N.H.R.; Yew, M.K.; Amalina, M.A.; Johan, M.R. (Maney Publishing, 2014)
This paper presents an investigation on solvent-borne intumescent flame-retardant coatings that can provide good bonding strength, water resistance and fire protection to the steel substrate. The fire protection performance and characterisations of the coatings were investigated by using the Bunsen burner test, thermogravimetry analysis, field emission scanning electron microscope, static immersion test and Instron Micro Tester. It was found that the fire protection and foam structure of the coating significantly improved by adding the combination of Mg(OH)(2) and TiO2 flame-retardant fillers to the flame-retardant additives and acrylic binder. The formation of uniform foam structure and reaction of the coating which decompose into voluminous and multicellular char layers with thermal insulation properties contribute an important fire protection to the steel substrate from reaching its critical temperature. However, the combination of [Al(OH)(3) and Mg(OH)(2)] flame-retardant fillers to the flame-retardant additives and epoxy binder led to maximum adhesion strength. The improvement in the bonding properties of the coating to the metal surface was attributed to the effective [Mg(OH)(2) and TiO2] fillers/epoxy binder interface adhesion. Hence, the findings of this study reveal that the selection of appropriate combination of binders and flame-retardant fillers strongly influenced the fire protection, water resistance and mechanical properties of intumescent coatings.